CLASP1, astrin and Kif2b form a molecular switch that regulates kinetochore-microtubule dynamics to promote mitotic progression and fidelity - Manning, Amity L (Nature Publishing Group, 2010)
Accurate chromosome segregation during mitosis requires precise coordination of various processes, such as chromosome alignment, maturation of proper kinetochore–microtubule (kMT) attachments, correction of erroneous attachments, and silencing of the spindle assembly checkpoint (SAC). How these fundamental aspects of mitosis are coordinately and temporally regulated is poorly understood. In this study, we show that the temporal regulation of kMT attachments by CLASP1, astrin and Kif2b is central to mitotic progression and chromosome segregation fidelity. In early mitosis, a Kif2b–CLASP1 complex is recruited to kinetochores to promote chromosome movement, kMT turnover, correction of attachment errors, and maintenance of SAC signalling. However, during metaphase, this complex is replaced by an astrin–CLASP1 complex, which promotes kMT stability, chromosome alignment, and silencing of the SAC. We show that these two complexes are differentially recruited to kinetochores and are mutually exclusive. We also show that other kinetochore proteins, such as Kif18a, affect kMT attachments and chromosome movement through these proteins. Thus, CLASP1–astrin–Kif2b complex act as a central switch at kinetochores that defines mitotic progression and promotes fidelity by temporally regulating kMT attachments.